Analysis of Utilitarian Ethics in Primary School Students' Use of Social Media : Analisis Etika Utilitarian dalam Penggunaan Media Sosial oleh Siswa Sekolah Dasar - Ohoiwutun, Barnabas; Sobon, Kosmas; Ohoitimur, Johanis (Jurnal Filsafat Indonesia, 2025)
This study aims to analyse the relationship between utilitarian ethics and the use of social media by primary school children. This paper critically examines the potential positive and negative effects of social media use for primary school children from the perspective of utilitarian ethics. The hermeneutic method is a philosophical method that examines, explores and seeks meaning for a particular concept. The researcher tries to reflect and interpret the study of utilitarian ethics while providing a sharp analysis of the issue in the context of social media use for primary school children. The results of the analysis show that utilitarian ethics can influence the behaviour and use of social media for primary school students. The implementation of utilitarian ethics has both positive and negative effects on children's social media behaviour. The value of utilitarian ethics can develop children's digital moral behaviour such as altruistic attitudes, positive cooperation, productive and responsible actions, social awareness, being critical of social issues, and engaging in online learning communities using social media. The results of this analysis are expected to provide philosophical contributions for students to use social media more responsibly, wisely and in accordance with universal moral values.